Hyers-Ulam Stability of Polynomial Equations - M. Bidkham; H. A. Soleiman Mezerji; M. Eshaghi Gordji (Abstract and Applied Analysis)
We prove the Hyers-Ulam stability of the polynomial equation 𝑎𝑛𝑥𝑛+𝑎𝑛−1𝑥𝑛−1+⋯+𝑎1𝑥+𝑎0=0. We give an affirmative answer to a problem posed by Li and Hua (2009).